A needs assessment for school social workers in Sierra Leone. (January 2019) - Bulanda, Jeffrey J; Jalloh, Sulaiman
This study explored social-emotional needs of pupils in Sierra Leone and supportive services that could address those needs. A total of 135 teachers and school administrators were surveyed. Descriptive statistics and themes from qualitative data are presented. Recommendations are made to deploy school social workers in Sierra Leone to (1) facilitate individual education planning, (2) counsel school pupils, (3) consult with school staff, (4) engage parents in the education of their children, and (5) serve as a liaison with community stakeholders. Sierra Leonean social workers should be capacitated to integrate international best practices with local knowledge to ensure culturally competent practice.